PROTOTIPE PEMBERI PAKAN IKAN DAN PENGGANTIAN AIR PADA AKUARIUM BERBASIS MIKROKONTROLER ATMEGA328P - Arta Darmika, Anak Agung; Raka Agung, I Gusti Agung Putu; Divayana, Yoga (Jurnal SPEKTRUM; Vol 6 No 2 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i02.p11, 2019)
Technological developments have encouraged many human lives in automatic matters. One of the uses of the rapidly developing electronics field is the application of household appliances. This study will be made a prototype of fish feed and water replacement in the aquarium of ATmega328P microcontroller based. This prototype aims to facilitate feeding of fish and replacing water in the aquarium. The sensor reading is using an ultrasonic sensor to control the amount of fish feed which when the feed runs out will be marked with a buzzer that lights up. The system for regulating fish feeding and replacement of water is regulated by the DS1307 Real Time Clock IC with a display in a 20x4 cm LCD. A valve opening for fish feed containers uses a servo motor. The program used in designing this prototype is to use the C Programming Language. The results achieved in this study are fish feed schedules and water changes can be arranged with a switch button with a twice daily feeding schedule and water replacement every three days. Another condition that is achieved is the servo motor and the water drain pump can work according to the schedule of the time that has been arranged. The conclusion of this research is that the prototype of fish feed and water replacement can already be implemented using the ATmega328P microcontroller. The fish feeder prototype can realize wave reflections from the ultrasonic sensor when the feed has run out, and it will automatically move the servo motor to open the valve, and the buzzer will sound if the fish feed is below 20%.